2013
DOI: 10.1371/journal.pone.0079126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Metabotropic Glutamate 1 Receptor Antagonist on Light Responses of Retinal Ganglion Cells in a Rat Model of Retinitis Pigmentosa

Abstract: BackgroundRetinitis pigmentosa (RP) is a progressive retinal degenerative disease that causes deterioration of rod and cone photoreceptors. A well-studied animal model of RP is the transgenic P23H rat, which carries a mutation in the rhodopsin gene. Previously, I reported that blocking retinal GABAC receptors in the P23H rat increases light responsiveness of retinal ganglion cells (RGCs). Because activation of metabotropic glutamate 1 (mGlu1) receptors may enhance the release of GABA onto GABAC receptors, I ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The finding in the present study that the D2/D3 receptor antagonists sulpiride and eticlopride transform long-latency ON-center cells into OFF-center cells suggests that these cells might have at one time been actually OFF-center cells. In retrospect this would account for the observations in my earlier studies [ 32 , 40 ] that OFF-center cells were encountered less frequently than ON-center cells in P23H rat retinas.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The finding in the present study that the D2/D3 receptor antagonists sulpiride and eticlopride transform long-latency ON-center cells into OFF-center cells suggests that these cells might have at one time been actually OFF-center cells. In retrospect this would account for the observations in my earlier studies [ 32 , 40 ] that OFF-center cells were encountered less frequently than ON-center cells in P23H rat retinas.…”
Section: Discussionmentioning
confidence: 55%
“…These cells can easily be missed if the retina is stimulated with a brief (e.g., 100 ms) flash of light, in which case these long-latency cells could appear to be OFF-center cells. Although in my previous electrophysiological studies in the P23H rat retina [ 32 , 40 ] I used long-duration flashes at the beginning of an experiment to classify cells as either ON- or OFF-center, it was assumed at the time that these long-latency cells were ‘unhealthy’ ON-center cells, recorded in areas of the retina that had perhaps undergone a greater degree of degeneration. The finding in the present study that the D2/D3 receptor antagonists sulpiride and eticlopride transform long-latency ON-center cells into OFF-center cells suggests that these cells might have at one time been actually OFF-center cells.…”
Section: Discussionmentioning
confidence: 99%
“…I previously found that both TPMPA and JNJ16259685 increase the sensitivity of P23H rat RGCs to brief flashes of light, shifting the intensity-response curves to the left [ 19 , 20 ]. A leftward shift of the intensity-response curve is equivalent to removing a neutral density filter in front of the light source.…”
Section: Resultsmentioning
confidence: 99%
“…TPMPA would eliminate this GABA-mediated inhibition and thus the attenuation of light-evoked excitatory potentials in the axon terminals of bipolar cells. Previously, I reported that the effects of JNJ16259685 on the responses of P23H rat RGCs to flashes of light are similar to those of TPMPA [ 20 ]. I had postulated that the effects of JNJ16259685 may be mediated through a reduction in release of GABA onto GABA C receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation